SERUM LEPTIN, SERUM ESTRADIOL AND BONE MINERAL DENSITY IN OBESE AND NON-OBESE POSTMENOPAUSAL WOMEN - Phyo, Nang-Ei; Hlaing, Chaw-Su; Sein, Mya-Thanda (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Osteoporosis is one of the major health issues in postmenopausal women. However, it has been reported that obesity is protective against osteoporosis. There are many evidences reporting that leptin and estrogen play a role in regulation of bone metabolism. Thus, leptin and extra-gonadal estrogen have a considerable role in osteoprotective effect in obese postmenopausal women. The present study aimed to investigate the serum leptin, serum estradiol and bone mineral density in obese and non-obese postmenopausal women. METHODOLOGY Non-obese (age=56±2.91 year; body mass index: BMI=22.39±2.12 kg/m2 ; n=30) and obese postmenopausal women (age=55.03±4.03 year; BMI=31.69±2.87 kg/m2 ; n=30) were recruited from Hlaing-Thar-Yar Township to participate in this cross-sectional analytical study. Serum leptin and estradiol levels were determined by enzyme-linked immunosorbent assay (ELISA) and bone mineral density (BMD) was determined by quantitative ultrasound (QUS). RESULTS Serum leptin, serum estradiol and BMD were significantly higher in obese than non-obese postmenopausal women (leptin: 13.81±5.11 vs 4.93±2.47 ng/ml, p<0.001; estradiol: 109.69±35.17 vs 87.65±37.86 pg/ml, p<0.05; BMD:0.10±1.20 vs-2.62±1.04, p<0.001). BMD had significant positive correlation with BMI in postmenopausal women (r=0.683, p<0.001, n=60). Serum leptin level had stronger correlation with BMD (r=0.6, p<0.001) than serum estradiol level (r=0.28, p<0.05). There is no correlation between serum leptin and serum estradiol levels. CONCLUSION Increased BMD in obese postmenopausal women might be due to increased serum leptin and serum estradiol levels considered as osteoprotective effects on bone metabolism. BMD had stronger association with serum leptin than serum estradiol levels and it indicated that serum leptin might have more important contribution in bone metabolism in postmenopausal women.